Programme of Work to Establish Guidelines for the Effective Administrative, Operation and Maintenance of the Irrigation and Drainage District in the BRUMEDEC PROJECT - Pizarro, Humberto (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
34 páginas